Semiotic Study in Java Community Political Disclosure in Gemolong District - Muhammad Wildan Sahidillah (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2020)
Language is an arbitrary sound symbol system that used for communication/interaction. Language is used as a communication tools in the political election. Political expression in the community of Jatibatur Village, contain signs that refers to certain things. The purpose of this study is to know: 1) political disclosure used people in Jatibatur Village, Gemolong Sub-district, and 2) the meaning of political disclosure used in Jatibatur Village, Gemolong Sub-district. The research method used in this research using an interview technique, see, and note. This study is a desriptive qualitative research. The data analysis technique in this study is using the analysys of the sign by Charles Sanders Pierce.  The result of this study are; 1) the existence of a Java lexicon, “abang” refers to PDI  perjuangan party, 2) the existence of a Java lexicon “wit ringin” refers to Golkar’s party in Indonesian, 3) the lexicon of a “wong cilik” in Java language especially in political, is refers to a poor people ora middle or lower class of people, 4) “ojo pedhot oyot” a tagline from PDI Perjuangan party in Centra Java, means to continuewhat was been fought, and 5) “caleg kae dekengane akeh” had a meaning that he had a strong protection.